DIDACTIC REQUIREMENTS FOR THE FORMATION OF PRIMARY INVARIANT AND VARIATIVE CONCEPTS ABOUT NATURE IN PRIMARY CLASS STUDENTS - Bobomurodov Sirojiddin Mengziyo o’g’li (American Journals, 2022)
In the article, methodological-didactic bases, principles, laws, psychological-pedagogical possibilities of forming the first invariant and variable concepts of nature in elementary school students, previous ideas on the formation of the first invariant and variable concepts of nature in elementary school students, formation of the first invariant and variable concepts of nature in students information about the different levels is given.
Keywords: primary class, invariant, variable, didactic principles, understanding, natural sciences